Smashing CSS : professional techniques for modern layout - Meyer, Eric A. (Chichester,West Sussex, U. K. : Wiley, 2011)
PROFESSIONAL TECHNIQUES FOR MODERN LAYOUT Smashing CSS takes you well beyond the basics, covering not only the finer points of layout and effects, but introduces you to the future with HTML5 and CSS3
1. Tools -- 2. Selectors -- 3. Tips -- 4. Layouts -- 5. Effects -- 6. Tables -- 7. The (near) future
Includes index
Keywords: Cascading style sheets; Layout (Printing); Web sites -- Design